Implementasi Aplikasi Reservasi Tiket Pada Hutan Pinus Kalilo Purworejo Berbasis Mobile - Setyaka, Galyleo Ilham; Wulandari, Sri; Handayani, Irma (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
Kalilo Pine Forest in Purworejo Regency, Central Java, is a tourist destination that offers visitors natural beauty and high comfort. However, the lack of popularity and information about the destination has made many people unfamiliar with it. In addition, the ticket sales system that still uses manual methods results in inconvenience for visitors. To overcome this problem, innovation is needed in the form of a mobile-based tourist ticket reservation application, utilizing the development of information technology and the phenomenon of increasing smartphone usage, especially in Indonesia. By using the waterfall research methodology and black box testing, this research aims to build a tourist ticket reservation application equipped with virtual tour features. It is expected that the results of this research will provide a better tourist experience to visitors and become a more effective and attractive promotional media.